DYNAMICS OF SYSTEMS ALLOWING STRUCTURAL PHASE TRANSITIONS - M. D. Ragushina; E. S. Savin (Тонкие химические технологии)
The dynamics of active atoms that determine structure phase transitions in a solid body is considered in the context of the previously presented atom interaction model based on a special type of three-minimum potential. Periodical and soliton-like solutions of nonlinear differential equation of motion were obtained. The value of the bond energy of active atoms with respect to the potential barrier height in a single-particle potential with a triple minimum determines the character of a phase transition. Crystals of the MeI MeIIBX4 kind, as well as crystals and metals, on the surface of which atoms of gases and metals are absorbed, are considered as objects, in which the obtained results can be used.